(untitled) (Bangladesh Critical Care Journal, 2022)
Background: Glucose variability is an indicator and independent predictors of mortality and severity of sepsis in critically septic patients of intensive care unit. Objectives: This study evaluated the relationship of glucose variability in critically ill septic patients in relation with serum lactate. Method: It is a prospective observational study was conducted in the Intensive Care Unit (ICU) in Department of Anesthesia, Pain, Palliative Care and Intensive Care, Dhaka Medical College hospital, Dhaka over a period of one year in between 1st January- 31st December, 2015. Total 51 septic adult patients were included in the study according to the selection criteria. In this study, 8 consecutive capillary blood samples were taken with a periodic interval of 3 hours starting from admission. Mean and standard deviation (SD) blood glucose were computed to see the glucose variability and agreement done with serum lactate and severity of sepsis. All collected data were registered documented and analyzed in the statistical program Statistical Package for Social Science (SPSS) version 20.0. Result: Among total 51 patients, 52.9% study cases were of 4th decade with a mean age of 46±12 years had a mild female predominance. Glycemic variability was taken as >2SD. High glycemic variability observed in 70.6% cases. Good agreement observed in glucose variability with serum lactate by Kappa Statistics. Conclusion: Glucose variability shows the prediction of sepsis and it could be used as a useful alternative tool to predict sepsis and severity of sepsis. Bangladesh Crit Care J March 2022; 10 (1): 10-14